2019
DOI: 10.1371/journal.pone.0225528
|View full text |Cite
|
Sign up to set email alerts
|

Testing Species Assignments in Extant Terebratulide Brachiopods: A Three-dimensional Geometric Morphometric Analysis of Long-Looped Brachidia

Abstract: Species of terebratulide brachiopods have been largely characterized qualitatively on the basis of morphology. Furthermore, species-level morphological variability has rarely been analyzed within a quantitative framework. The objective of our research is to quantify morphological variation to test the validity of extant named species of terebratulide brachiopods, focusing on the lophophore-supporting structures—the “long loops.” Long loops are the most distinctive and complex morphological feature in terebrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…From our previous studies (López Carranza and Carlson 2019), we concluded that we can quantitatively and reliably discriminate extant species based on long-loop brachidial morphology. However, delicate internal morphology, including brachidia, is rarely preserved in fossils.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…From our previous studies (López Carranza and Carlson 2019), we concluded that we can quantitatively and reliably discriminate extant species based on long-loop brachidial morphology. However, delicate internal morphology, including brachidia, is rarely preserved in fossils.…”
Section: Discussionmentioning
confidence: 70%
“…7), indicating that these two species are more similar in shape than either is to L. vancouveriensis , even though L. erythraeus and L. vancouveriensis are both eastern Pacific species. Although they occur on opposites sides of the Pacific Ocean, L. erythraeus and L. rubellus were collected from similar latitudes and possibly similar temperature regimes (López Carranza and Carlson 2019). The similarity in outlines between L. erythraeus and L. rubellus is also visible in their mean outline shapes, shown in Figure 6.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations